Novi trendi v kirurškem zdravljenju kronične venske insuficience na spodnjih udih - Valentinuzzi, Vladimir (Zdravniški vestnik, 2002)
Background. Chronic venous insufficiency is the disease of modern world. Indications for surgical treatment of varicose veins are reviewed. Elucidated are methods of extirpation of varicose veins, safenofemoral and safenopopliteal ligature. Conclusions. Short striping by invagination is recommended. Subfascial perforant vein surgery is described. Methods of conservative and operative treatment of deep venous insufficiency are reviewed.
Keywords: kirurško zdravljenje; kronična venska insuficienca; Safenska vena; Saphenous vein; Surgery; Varice; Varicose ulcer; Varicose veins; Varikozni ulkus; Vasectomy; Vazektomija; Venous insufficiency; Venska insuficienca